Enhancing 21st Century Skills: Innovative Education and Career Preparedness For Students - Ni Km. Nidyantari Laksmi R.; I Nyoman Adi Jaya Putra; Dewa Putu Ramendra; Made Hery Santosa (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze innovative educational strategies that support the development of 21st-century skills and career preparedness for students through a systematic literature review. Skills such as critical thinking, collaboration, creativity, and digital literacy are essential in addressing global challenges. This research identifies best practices in education that integrate technology, project-based learning, and collaborative approaches to enhance these skills. The findings highlight the importance of technology-based curricula, soft skills training, and partnerships between educational institutions and industries. This article provides recommendations for educators and policymakers to improve the effectiveness of 21st-century education.